Diving into Inflammation: A Pilot Study Exploring the Dynamics of the Immune–Microbiota Axis in Ileal Tissue Layers of Patients with Crohn's Disease. (21st February 2021) - Russo, Edda; Giudici, Francesco; Ricci, Federica; Scaringi, Stefano; Nannini, Giulia; Ficari, Ferdinando; Luceri, Cristina; Niccolai, Elena; Baldi, Simone; D'Ambrosio, Mario; Ramazzotti, Matteo; Amedei, Amedeo
Abstract: Background and Aims: The pathogenesis of Crohn's disease [CD] is still unclear. Disorders in the mucosal immunoregulation and its crosstalk with the microbiota may represent an important component in tissue injury. We aimed to characterize the molecular immune response distribution within the ileal layers and to evaluate the correlated microbiota in pathological/healthy settings comparing first surgery/relapse clinical conditions. Methods: We enrolled 12 CD patients. A comprehensive analysis of an ileal mucosa, submucosa and serosa broad-spectrum cytokine panel was performed through a multiplex approach. In addition, ileal microbiota composition was assessed through next generation sequencing. Results: We observed a distinct profile [of IL1-α, IL-1β, IL-4, IL-8, ICAM-1, E-Selectin, P-Selectin, IP-10, IL 6 and IL 18] across the CD vs healthy ileal layers; and a different distribution of IFN- γ, P-Selectin, IL-27 and IL-21 in first surgery vs relapse patients. In addition, the phylum Tenericutes, the family Ruminococcaceae, and the genera Mesoplasma and Mycoplasma were significantly enriched in the pathological setting. Significant microbiota differences were observed between relapse and first surgery patients regarding the class Bacteroidia, and the genera Prevotella, Flavobacterium, Tepidimonas and Escherichia/Shigella. Finally, the abundance of the genus Mycoplasma was positively correlated with IL-18. Conclusions: We describe a dissimilarity of cytokine distribution and microbiota composition within CD and adjacent healthy ileal tissue layers and between first operation and surgical relapse. Our results give potential insight into the dynamics of the gut microbiota–immune axis in CD patients, leading to detection of new biomarkers.